A memória cultural sergipana na perspectiva do Departamento de Cultura e Patrimônio Histórico (DCPH, 1970-1975) - Oliveira, Raianne Pereira de (2019)
The present research aims to understand the process of construction and formalization of the Sergipe cultural memory based on the work developed by the Department of Culture and Historical Heritage (DCPH), a state preservation public policy created and active in Sergipe in the context of the civil-military dictatorship , specifically, in the period 1970-1975. The search for the means to legitimize itself and concerned with the direction of cultural production in the country after 64, the authoritarian state began to invest heavily in the construction of a "patrimonialist" cultural policy whose priority, of course, was to expand the existing, but lagging protection system of the "National Historic and Artistic Heritage" (concentrated only and exclusively around the DPHAN (current IPHAN) since 1937). The solution to this problem was studied and condensed in the "Brasília Commitment" (1970), a document produced by the MEC, which recommended the creation of cultural organs in all states as a way to decentralize preservation actions in Brazil. In addition to culturally and economically enhancing the region, this direct intervention of the state in the area was aimed at awakening society towards civility, bringing it closer to the symbols and representations of national culture. Seeking to understand the particularities that involve the trajectory of the DCPH in Sergipe (the conditioning factors, social agents involved, guidelines, actions and challenges), this research uses as reference studies on the construction of memory and patrimony contemporaneity and is based on the analysis of official documents, photographs, periodicals, as well as oral history methodology.